The Role of Multimedia on Virtual Teachers in the Digital Era to Carve the Educational Future of Indonesia's Golden Generation - Derin Asyri; Devan Asyri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This research investigates the implications and complications resulting from collective disruption in education, especially in the learning process. Factors driving this disruption include globalization and Industrial Revolution 4.0 (including Society 5.0), demands for Sustainable Development Goals, and the incessant COVID-19 pandemic. The importance of multimedia digital era so that they are not hampered in carrying out their mandate due to the transition from offline to online learning. And coverage for students and parents so that they do not stutter suddenly as an implication of a shift in learning mode. Methodologically, this research uses a qualitative approach, especially an integrative review. After going through four stages of the procedural process (Design, Implementation, Analysis, and Writing Results and Review), this research succeeded in informing the four basics of being a virtual teacher in the digital era. One: Ten Characteristics of Virtual Teachers in the Digital Age. Two: Transform yourself into a true virtual teacher according to the demands of 21st-century learning (cultural, functional, and digital transformation). Three: Proficient in three virtual teacher technical skills to build Indonesia's golden generation (skills in developing interactive digital learning modules, packaging virtual-digital learning delivery, and compiling online learning assessments). Fourth: Master practical tips for becoming a virtual teacher (developing the golden generation, applying a growth mindset perspective) so that you are always adaptive to any changes, especially in the scope of education.